USING SPECULATIVE DESIGN TO REIMAGINE DIGITAL PERIOD TRACKING FOR THE GLOBAL MAJORITY - B, Arathy S (AoIR Selected Papers of Internet Research, 2026)
Digital period tracking, facilitated by apps, wearables, and digital health platforms, has largely been examined through a Global North-centric lens. This paper shifts focus to India, where menstruators navigate period tracking within deeply stratified socio-digital environments marked by caste, class, gender, and infrastructural inequalities. While period-tracking apps are positioned as tools for reproductive autonomy, they often reinforce gendered surveillance, datafication, and exclusionary design practices.By centering the experiences of caste-marginalized, queer, and rural menstruators, this research interrogates the socio-cultural conditions shaping digital menstrual health technologies. Drawing on in-depth interviews and participatory speculative design (PSD) as a methodological approach, the study critically examines how menstruators engage with and navigate digital period tracking.Despite the promise of digital reproductive health technologies, this paper argues that period-tracking apps in India exist within a broader landscape of social and technological inequities. Identity markers such as caste, gender, and class significantly impact digital access, shaping who can engage with these technologies and under what conditions. Moreover, the lack of robust data protection laws raises concerns about privacy, surveillance, and the commodification of menstrual health data.By critically examining digital period tracking through a Global Majority perspective, this paper contributes to discussions on self-tracking, technological justice, and digital health equity. It calls for a reimagining of menstrual technologies that are inclusive, culturally relevant, and designed with—not just for—marginalized menstruators.